THE 6‐minute walk test and other endpoints in Duchenne muscular dystrophy: Longitudinal natural history observations over 48 weeks from a multicenter study. Issue 3 (26th June 2013) - Mcdonald, Craig M.; Henricson, Erik K.; Abresch, R. Ted; Florence, Julaine M.; Eagle, Michelle; Gappmaier, Eduard; Glanzman, Allan M.; ,; Spiegel, Robert; Barth, Jay; Elfring, Gary; Reha, Allen; et al.
ABSTRACT Introduction: Duchenne muscular dystrophy (DMD) subjects ≥5 years with nonsense mutations were followed for 48 weeks in a multicenter, randomized, double‐blind, placebo‐controlled trial of ataluren. Placebo arm data (N = 57) provided insight into the natural history of the 6‐minute walk test (6MWT) and other endpoints. Methods: Evaluations performed every 6 weeks included the 6‐minute walk distance (6MWD), timed function tests (TFTs), and quantitative strength using hand‐held myometry. Results: Baseline age (≥7 years), 6MWD, and selected TFT performance are strong predictors of decline in ambulation (Δ6MWD) and time to 10% worsening in 6MWD. A baseline 6MWD of <350 meters was associated with greater functional decline, and loss of ambulation was only seen in those with baseline 6MWD <325 meters. Only 1 of 42 (2.3%) subjects able to stand from supine lost ambulation. Conclusion: Findings confirm the clinical meaningfulness of the 6MWD as the most accepted primary clinical endpoint in ambulatory DMD trials. Muscle Nerve48: 343–356, 2013